Bridging the Gap: Greater Usability for TEI encoding - Stefan Dumont (OpenEdition, 2015)
This article shows how, with a focus on user-friendliness and a bottom-up approach, the digital work environment ediarum was successfully developed. With ediarum, researchers can comfortably encode and edit in TEI, as well as publish their results in an online or print edition. This solution, developed by the TELOTA initiative of Berlin-Brandenburg Academy of Sciences and Humanities, is based on three software components: eXistdb, Oxygen XML Author, and ConTeXt. These components are combined, supplemented with additional functions, and tailored to fit a project’s needs. After a pilot run, ediarum has been implemented for multiple internal and external research projects. The experience that was gained and our self developed program components are available to the Digital Humanities community.